Measuring pH in low ionic strength glacial meltwaters using ion selective field effect transistor (ISFET) technology. (27th January 2021) - Bagshaw, Elizabeth A.; Wadham, Jemma L.; Tranter, Martyn; Beaton, Alexander D.; Hawkings, Jon R.; Lamarche‐Gagnon, Guillaume; Mowlem, Matthew C.
Abstract: Measuring pH in glacial meltwaters is challenging, because they are cold, remote, subject to freeze‐thaw cycles and have low ionic strength. Traditional methods often perform poorly there; glass electrodes have high drift and long response times, and spectrophotometric techniques are unpractical in cold, remote environments. Ion selective field effect transistor (ISFET) sensors are a promising alternative, proven in marine and industrial applications. We assess the suitability of two models of ISFET, the Honeywell Durafet and Campbell Scientific Sentron, for use in glacial melt through a series of lab and field experiments. The sensors have excellent tolerance of freeze‐thaw and minimal long‐term drift, with the Durafet experiencing less drift than the Sentron model. They have predictable response to temperature, although the Durafet housing causes some lag during rapid cycling, and the impact of stirring is an order of magnitude less than that of glass electrodes. At low ionic strength (< 1 mmol L −1 ), there is measurable error, but this is quantifiable, and less than glass electrodes. Field tests demonstrated low battery consumption, excellent longevity and resistance to extreme conditions, and revealed biogeochemical processes that were unlikely to be recorded by standard methods. Meltwater pH in two glacial catchments in Greenland remained > 7 with consistent diurnal cycles from the very first meltwater flows. We recommend that ISFET sensors are used to assess the pH of glacial meltwater, since their tolerance is significantly better than alternative methods: the Durafet is accurate to ± 0.2 pH when waters are > 1 mmol L −1 ionic strength, and ± 0.3 pH at < 1 mmol L −1 .